2021
DOI: 10.1111/hsc.13382
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, practices and fear of COVID‐19 among Iranians: A quick online survey

Abstract: To control COVID‐19, several strategies were proposed in Iran since the start of the outbreak. The number of reported infected people and its consequent death toll herald relative inadequacies in the quality and extent of the measures in curbing the COVID‐19 transmission cycle. This study was conducted to investigate knowledge, attitude, precautionary practices and degree of fear related to COVID‐19 in a sample of Iranian population. This study was conducted among 457 residents of Kurdistan Province, Iran, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“… Turkey Europe Medical 47.39 Collectivism Elsayed and Ghazi, 2021 275 6.5 Egypt Middle East Healthcare students N.A. Collectivism Ghaderi et al, 2021 457 4.5 Iran Middle East General population 37.86 Collectivism Grande and Doyle-Baker, 2021 680 13.5 Canada North America University students 23 Individualism Green et al, 2021 608 9 Pakistan Asia University students 24.76 Collectivism Gélinas et al, 2021 1517 N.A. Canada North America Hospital staff 41.11 Individualism Jafari-Oori et al, 2021 350 N.A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Turkey Europe Medical 47.39 Collectivism Elsayed and Ghazi, 2021 275 6.5 Egypt Middle East Healthcare students N.A. Collectivism Ghaderi et al, 2021 457 4.5 Iran Middle East General population 37.86 Collectivism Grande and Doyle-Baker, 2021 680 13.5 Canada North America University students 23 Individualism Green et al, 2021 608 9 Pakistan Asia University students 24.76 Collectivism Gélinas et al, 2021 1517 N.A. Canada North America Hospital staff 41.11 Individualism Jafari-Oori et al, 2021 350 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies conducted in Europe, female's COVID-19 related fear and anxiety levels were higher ( Bakioğlu et al, 2020 ; Kaçoğlu et al, 2021 ; Morales-Rodríguez, 2021 ; Orrù et al, 2021 ; Tsipropoulou et al, 2020 ; Ypsilanti et al, 2021 ). On the other hand, some studies conducted in Middle East countries showed that males had higher levels of COVID-19 related fear and anxiety than females ( Abdelgwad and Abdelaziz, 2021 ; Alnazly et al, 2021 ; Ashoor et al, 2021 ; Ghaderi et al, 2021 ; Saravanan et al, 2020 ). These studies revealed inconsistent findings regarding gender differences in COVID-19 related fear and anxiety across different continents.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One such negative emotion that has been highly associated with the current COVID‐19 is the high amount of fear (Ahorsu et al., 2020b ; Taghrir et al., 2020 ). There is ample evidence about the impact of fear on quality of life and mental health (Al Falasi & Ab Khan, 2020 ; Ghaderi et al., 2021 ). Medical students are often found resilient; however, they are not immune to such fears.…”
Section: Introductionmentioning
confidence: 99%
“…Positive attitudes towards following physical distancing, taking precautionary measures against community spread, and relying on science-driven evidence help people resist false propaganda or misinformation during this unprecedented time. Appropriate practicing of preventive tactics and accepting local behavioral recommendations may substantially assist the globally synchronized mitigation efforts [11].…”
Section: Introductionmentioning
confidence: 99%